Article Withdrawal by ASERS Publishing - Fraudulent double submission and legal limitations - Ecologization of Agroindustrial Production: Organizational and Economic Transformations - FROLOVA, Irina; VORONKOVA, Olga; ISLAMUTDINOVА, Dina; GORDEYEVA, Olga; FEDULOVA, Inna; ZHMINKO, Albina (Journal of Environmental Management and Tourism, 2019)
The increase in the production of agricultural products and food supplies in excess of regulatory needs and the provision of food safety in Russia led to the expansion of the export of agricultural products and the change in the course of the development of the agro-industrial complex from import substitution to export-oriented production. However, the entry to world food markets requires high quality of products from manufacturers and its certification in accordance with world standards. The article presents the organizational and economic transformations towards the greening of agro-industrial production, namely, the use of the resource potential, the involvement of Russian manufacturers in the production of environmentally friendly products and the development of organic agriculture; the mechanisms for solving the set problems are substantiated.